PSB in Bhutan: Countering Foreign Invasion with Local Contents - Wangmo, Dechen; Yesudhasan, Thomas (Manipal Academy of Higher Education, 2019)
Bhutan has been a latecomer to the world of public service broadcasting (PSB). As the global debate on whether there still is a place for PSB in the changing media landscape is continuing, Bhutan, on the contrary, is working towards strengthening its PSB. There are compelling reasons why Bhutan seeks to strengthen its PSB. As the isolated Himalayan kingdom is bombarded with over 50 international satellite TV channels, PSB is an important source of news and information for the Bhutanese audience. It plays an ever more critical role in strengthening the country’s nascent democracy by providing the public a platform to voice their concerns and debate and discuss various social, political, cultural and economic issues. Also, as the only local or national TV channel, it plays a crucial role in counterbalancing the flood of foreign programming beamed into the country and protect Bhutan’s unique Buddhist culture and nurture it for the 21st century.